Minimizing harmonic distortion impact cause by CS using meta heuristic technique - S. N. Syed Nasir; J. J. Jamian; M. W. Mustafa (Universitas Ahmad Dahlan, 2019)
Non-linear load in the distribution system has caused negative impact to its power quality especially on harmonic distortion. Charging Station (CS) is a non-linear load that widely promoted with the aim to support the continuous usage of Electric Vehicle (EV). This research is focusing on optimal placement and sizing of multiple passive filter to mitigate harmonic distortion due to CS usage at distribution system. There are 6 units of CS which being placed in low voltage buses which indirectly will inject harmonic to the system during charging. Power system harmonic flow, passive filter, CS, battery and the analysis will be model in MATLAB. Multi-objective function which are weight summation approach (WSA) and Pareto Front are used to assist meta heuristic technique which is Modified Lightning Search Algorithm (MLSA) to identify optimum location and sizing of passive filter based on improvement on propose five parameters. From the result, the optimal placements and sizing of passive filter able to reduce the maximum Total Harmonic Distortion (THD) for voltage, current and apparent losses respectively. Therefore, the propose method is suitable to reduce harmonic distortion as well as apparent losses at distribution system with present of CS.